Corneal reshaping and myopia progression. Issue 9 (4th May 2009) - Walline, J J; Jones, L A; Sinnott, L T
Abstract : Background/aims: Anecdotal evidence indicates that corneal reshaping contact lenses may slow myopia progression in children. The purpose of this investigation is to determine whether corneal reshaping contact lenses slow eye growth. Methods: Forty subjects were fitted with corneal reshaping contact lenses. All subjects were 8 to 11 years and had between −0.75 D and −4.00 D myopia with less than 1.00 D astigmatism. Subjects were age-matched to a soft contact lens wearer from another myopia control study. A-scan ultrasound was performed at baseline and annually for 2 years. Results: Twenty-eight of 40 (70%) subjects wore corneal reshaping contact lenses for 2 years. The refractive error and axial length were similar between the two groups at baseline. The corneal reshaping group had an annual rate of change in axial lengths that was significantly less than the soft contact lens wearers (mean difference in annual change = 0.16 mm, p = 0.0004). Vitreous chamber depth experienced similar changes (mean difference in annual change = 0.10 mm, p = 0.006). Conclusion: Results confirm previous reports of slowed eye growth following corneal reshaping contact lens wear.